2012
DOI: 10.5187/jast.2012.54.5.341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Flammulina velutipes Mycelium on Broiler Chick Performance, Pathogenic Bacterial Counts in Caecal Contents and Amount of NH3in Excreta

Abstract: The purpose of this study was to evaluate the effects of dietary Flammulina velutipes mycelium (FVM) on broiler chick performance, pathogenic bacterial (E. coli, Salmonella) counts in caecal contents and amount of NH3 in excreta. Ninety-six broiler chicks (HanHyup No. 3, Korea) were divided into four groups: 1) Control (basal diet), 2) T1 (supplemented with 1% FVM), 3) T2 (3% FVM), and T3 (5% FVM), and rose for 7 weeks. In results, there were no significant differences among treatments in weight gain, feed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
4
3
0
Order By: Relevance
“…reported that fermented F. velutipes mycelium had no significant effects on feed intake and FCR in laying hens. In addition, Lee et al . stated that 5% F. velutipes mycelium did not improve feed intake in broilers, which was similar to the results of the present study with respect to feed intake.…”
Section: Discussionsupporting
confidence: 91%
“…reported that fermented F. velutipes mycelium had no significant effects on feed intake and FCR in laying hens. In addition, Lee et al . stated that 5% F. velutipes mycelium did not improve feed intake in broilers, which was similar to the results of the present study with respect to feed intake.…”
Section: Discussionsupporting
confidence: 91%
“…In addition Na et al [ 22 ] reported that inclusion of F. velutipes media at 5% to 10% in layer diets had no significant effects on egg production, egg weight, egg mass, and FCR. Lee et al [ 18 ] reported that higher levels up to 5% F. velutipes mycelium did not improve feed intake in broiler which was similar with the current study for feed intake. Unmarketable eggs were significantly lower in 4% FVW and 6% FVW fed groups, which was associated with higher calcium deposition in egg shell with dietary inclusion of FVW in the experimental groups.…”
Section: Discussionsupporting
confidence: 89%
“…Demand for applying medicinal and functional natural herbs in chicken rations is increasing to improve health status as well as production performance after the ban of antimicrobial growth promoters (antibiotics) in different countries [ 17 ]. The estimated value of DM, crude protein (CP), crude fiber (CF) in FVW were mostly close to previously reported values [ 18 , 19 ] but EE, calcium and phosphorus were lower than the published values (EE, 18.4 to 73.3 g/kg; calcium 4.6 to 11.8 g/kg; and phosphorus 8.8 to 9.4 g/kg) [ 19 , 20 ]. These differences were associated with effects of soil, cultivation methods and environmental factors.…”
Section: Discussionsupporting
confidence: 86%
“…These findings were similar to Zeng et al (2016), who reported that the diversity of cecal microflora in broilers was significantly higher in FVS supplemented diets than in the control. Some past studies found that FVS could increase the beneficial bacteria and could decrease the harmful bacteria (Lee et al, 2012;Lee et al, 2014). In this study, the FVS groups did not contain the pathogenic species Helicobacter pullorum (Steinbrueckner et al, 1997) and Alistipesfinegoldii (Dziarski et al,2016) which were found in the HS group only.…”
Section: Effect Of Fvs On the Microbial Diversitymentioning
confidence: 59%
“…Laying hens fed with FVS (3-5%) could reduce the pathogenic bacteria like Salmonella spp., E. coli and Clostridium spp., as well as increase the number of beneficial bacteria of Lactobacillus spp., and Bifidobacterium spp. (Lee et al, 2012;Lee et al, 2014). However, there was no previous study on the effect of Flammulinavelutipess tem base on animals submitted to heat stress.…”
Section: Effects Of Flammulinavelutipes Stem Base On Microflora and Vmentioning
confidence: 99%